2015
DOI: 10.15408/ijee.v1i1.1196
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Errors in the Third Singular Pronouns of Simple Present Tense by Using Interlanguage Analysis as an Approach. A Case Study

Abstract: The purpose of this study is to analyze factors contributing to errors made in learning English as a target language (TL). Employing a case study research, the participant was interviewed for approximately 30 minutes about daily activities and experiences in learning English. This research focuses in analysing the participant"s use of third singular pronoun in simple present tense. The findings revealed that errors made by TL learners are mainly influenced by some factors related to their TL"s and native langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Zawahreh (2012) offered an in-depth analysis and concluded that the errors arose from intrusion in the first and in-between languages. The study of Pandarangga (2014) also discovered that learners often omit verb agreement by using the simple present tense in the third singular pronouns. When the participant attempted to invent a modern language structure that contrasted with his natural language, errors resulted.…”
Section: Types Of Errors In Writingmentioning
confidence: 97%
“…Zawahreh (2012) offered an in-depth analysis and concluded that the errors arose from intrusion in the first and in-between languages. The study of Pandarangga (2014) also discovered that learners often omit verb agreement by using the simple present tense in the third singular pronouns. When the participant attempted to invent a modern language structure that contrasted with his natural language, errors resulted.…”
Section: Types Of Errors In Writingmentioning
confidence: 97%
“…Furthermore, Pandarangga's (2015) found that an EFL student tended to omit verb-agreement when he used the simple present tense in the third singular pronouns. Errors occurred because the participant was trying to invent a new language system that correlates with his native language.…”
Section: Introductionmentioning
confidence: 99%